2002
DOI: 10.1034/j.1399-6576.2002.460216.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative muscle paralysis after rocuronium: less residual block when acceleromyography is used

Abstract: Clinical evaluation of recovery of neuromuscular function does not exclude significant residual paralysis following the intermediate-acting muscle relaxant rocuronium, but the problem of residual block can be minimized by use of AMG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 26 publications
2
59
0
3
Order By: Relevance
“…Many studies have observed that monitorization of neuromuscular transmission decreases the frequency of PORC (16,17). It is recommended that monitorization of neuromuscular transmission be performed primarily in elderly patients, in dysfunction of the kidney and liver, in patients with cardiovascular disease and asthma, in diseases involving neuromusculoskeletal system, in those who are morbidly obese, and in long lasting surgical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have observed that monitorization of neuromuscular transmission decreases the frequency of PORC (16,17). It is recommended that monitorization of neuromuscular transmission be performed primarily in elderly patients, in dysfunction of the kidney and liver, in patients with cardiovascular disease and asthma, in diseases involving neuromusculoskeletal system, in those who are morbidly obese, and in long lasting surgical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Bununla birlikte Gatke ve ark. [15] orta etkili bir kas gevşetici ajan olan roküronyuma bağlı rezidüel bloğun nöromusküler monitörizasyonla minimalize edilebileceğini bildirmişlerdir. Bizim olgumuzda hem intraoperatif nöromusküler monitörizasyon uygulanmamasının hem de orta etkili bir kas gevşetici olmasına rağmen roküronyumun infüzyon şeklinde kullanılmasının postoperatif rezidüel bloğa neden olabileceğini düşünüyoruz.…”
Section: Discussionunclassified
“…La incidencia de BNMR presenta una gran variabilidad con porcentajes que oscilan entre el 2% y el 64% 87,93,94,95,96,97,98,99,100,101,102,103,104,105 .…”
Section: Incidencia De Bnmrunclassified